Speech acts and phrases of knowledge construction in asynchoronous discourse / Alice Shanthi... [et al.] - Alice, Shanthi; Xavier, Thayalan; Jane, Xavierine; Hamuddin, Budiando (Universiti Teknologi MARA, Negeri Sembilan, 2017)
This paper presents the findings of a study conducted in Malaysia pertaining to the speech acts commonly used for information sharing in web-forums. Data was purposively selected from online forums to answer the research questions. The messages in the data were categorised based on Searle’s (1976) Speech Acts taxonomy to explore the interactive language function of the messages. The study found that online forum members used more speech acts that were categorised as assertive in their web-forum interaction. The study also revealed different phases of knowledge construction were also present in the messages posted in web-forums. The findings of this study hopes to aid educators and academicians in the pedagogical aspect in using online discussion forums in the teaching and learning process.